The Game and Impetus Analysis of Ecological Enrichment of Corporate Citizens - Wanting Li; Yongling Ye; Yumei Ning (Discrete Dynamics in Nature and Society)
Ecological enrichment is not the growth of the economic value of a business entity and the use of surplus to fund deficits, but the coordinated growth of corporate citizens’ ecological value and economic value, which is conducive to the positive evolution of ecological beauty and economic vitalization. Through the game model, this paper makes a game analysis of various possibilities of the game of ecological enrichment and further gives a balanced solution to the impetus of ecological enrichment. Positive-sum return, return equilibrium, and dynamic equilibrium are all the necessary conditions for the positive selection of repeated games for corporate citizens’ ecological enrichment and play a decisive role in the impetus of ecological enrichment.